Financial Inclusion in the Maldives : Findex 2018 Survey - World Bank Group (World Bank, Washington, DC, 2019)
In this note authors explore the many ways that adults in the Maldives are using digital payment services through mobile phones, the internet, and bank accounts. The authors also explore savings habits and outline opportunities to use digital technology to bring financial services to adults who still have no accounts. The Findex Notes series summarizes data compiled by the Global Findex from nationally representative surveys of more than 150,000 adults in over 140 economies in 2017, including more than 1,000 adults in the Maldives. Research is showing that when people embrace digital financial services, a range of development benefits follow. When women in India received personal accounts linked to a jobs guarantee program, they increased their labor force participation and earnings compared to women who received such payments into a join account controlled by their husbands. The improvements in employment and earnings improvements disproportionately benefitted women with previously low labor force participation and those whose husbands were most opposed to their getting a job. Women-headed households in Nepal spent 15 percent more on nutritious foods (meat and fish) and 20 percent more on education after receiving free savings accounts. Another study found that the adoption of mobile money accounts in Kenya helped lift 194,000 people out of poverty, and that the accounts proved especially beneficial for women. Mobile money has also been cited as a fast and efficient method of sending and receiving funds from a network of acquaintances during an emergency, potentially reducing the likelihood that those impacted by a financial crisis will descend into poverty.